INNOVATIVE ECONOMY AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF RURAL TERRITORIES OF KAZAKHSTAN - M.E.Munasipova,; A.Т. Abdykarimova,; A.N. Narenova,; Zh.M. Omarhanova,; D.A. Amerzhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
The rural economy of Kazakhstan experienced a structural crisis caused by a break in the inter-industry ties necessary for balanced and sustainable development, which was accompanied by an imbalance between the production of important types of products and their needs. The key task of the state policy of Kazakhstan is the revival of the countryside, the solution of which is carried out on the basis of improving the development policy of rural territories, searching for new ideas and directions for the qualitative development of the countryside. Along with this, there are factors hindering the achievement of sustainable development of rural territories, among which there is a persistent low labor productivity and insufficient level of economic efficiency of production activities.